(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
Unsteady hydromagnetic Couette flow of a viscous incompressible electrically conducting fluid in a rotating system is studied when the fluid flow within the channel is induced due to the impulsive movement of the one of the plates of the channel. The plates of the channel are considered porous and the magnetic field is fixed relative to the moving plate. Exact solution of the governing equations is obtained by Laplace transform technique. The expression for the shear stress at the moving plate is also obtained. Asymptotic behaviour of the solution is analyzed for small as well as large values of time t to highlight the transient approach to the final steady state flow and the effects of rotation, magnetic field and suction/injection. It is found that suction has retarding influence on the primary as well as secondary flow where as injection and time have accelerating influence on the primary and secondary flows.